Word Order in the Clause Structure of Syrian Akkadian. Diss. - Finley, T. J.
director G. Buccellati; Order No. 7921393; order SOV versus VOS in 14th-12th century Syria; Diss Abstr 40 (1979-1980) 2033f.-A.